The use of platelet-rich fibrin in the surgical treatment of medication-related osteonecrosis of the jaw: 40 patients prospective study - Zelinka, Jiri; Blahak, Jiri; Perina, Vojtech; Pacasova, Rita; Treglerova, Jana; Bulik, Oliver (Biomedical papers, 2021)
Objectives. Medication-related osteonecrosis of the jaw (MRONJ) is defined as exposed bone in the maxillofacial region persisting for more than eight weeks in patients who are or were treated with antiresorptive or antiangiogenic agents and had no radiation therapy to the craniofacial region or obvious metastatic disease of the jaws. It is a recognised side effect of antiresorptive or antiangiogenic medication. To date, there is no specific gold standard treatment for MRONJ cases. The aim of this study was to evaluate the successful rate of surgical treatment with adjuvant local application of platelet rich fibrin. Methods. 40 patients treated with necrotic bone resection and adjuvant local application of platelet-rich fibrin (PRF) were included. Treatment outcomes were evaluated after 12 months. Results. The outcome of surgical treatment was successful in 34 of all 40 patients (85%), in 12 months follow-up. If we evaluate only cases where removal of all necrotic bone was possible the success rate was increased to 94%. A significant association between size of necrotic bone and treatment response was found (P=0.014, Wilcoxon rank sum test with continuity correction). Conclusions. Surgical treatment of MRONJ with adjuvant local PRF application proved to be very effective and safe, especially in early stages when all necrotic bone can be easily removed.
Keywords: medication related osteonecrosis of the jaw; platelet rich fibrin; surgical treatment